login
A079357
a(1)=1; a(n)=a(n-1)-1 if n is already in the sequence, a(n)=a(n-1)+4 otherwise.
4
1, 5, 9, 13, 12, 16, 20, 24, 23, 27, 31, 30, 29, 33, 37, 36, 40, 44, 48, 47, 51, 55, 54, 53, 57, 61, 60, 64, 63, 62, 61, 65, 64, 68, 72, 71, 70, 74, 78, 77, 81, 85, 89, 88, 92, 96, 95, 94, 98, 102, 101, 105, 104, 103, 102, 106, 105, 109, 113, 112, 111, 110, 109, 108, 107
OFFSET
1,2
COMMENTS
If, in the defining recurrence, the rule a(n)=a(n-1)+4 when n is not already in the sequence is generalized to a(n)=a(n-1)+k, then the resulting sequence ultimately becomes periodic with period 1,3,10,35 for k=1,2,3,4, respectively. - John W. Layman, Apr 15 2003
FORMULA
It appears that, for n >= 219, a(n)=n+b(n) where b(n) is the period-35 sequence (-1, 2, 5, 3, 6, 9, 7, 5, 8, 11, 9, 12, 10, 8, 6, 9, 7, 10, 13, 11, 9, 7, 5, 3, 1, -1, -3, -5, -7, -9, -11, -13, -10, -7, -4).
CROSSREFS
KEYWORD
nonn,easy
AUTHOR
Benoit Cloitre, Feb 14 2003
EXTENSIONS
More terms from John W. Layman, Apr 15 2003
STATUS
approved